How does financial inclusion influence environmental sustainability in Saudi Arabia? - Abdulmajeed Mhali Alshammari (Energy Strategy Reviews)
Financial Inclusion (FI) can increase access to financial resources, which can give rise to environmental problems if financial resources are not utilized for renewable projects. Thus, this research aims to empirically test the effect of FI on the environment in the fossil fuel-dependent Saudi economy. For this purpose, the effect of FI on CO2 emissions is tested in the Environmental Kuznets Curve (EKC) framework by using the autoregressive distributive lag technique and by using a period 1980–2021 in Saudi Arabia. The results substantiate the EKC hypothesis in the long and short run with a turning point of income per capita at Saudi Riyals 123,297 and 123,355, respectively. So, economic growth does have environmental problems in the Kingdom as per the average income per capita during the sample period. FI raises emissions in the long and short runs. However, Foreign Direct Investment (FDI) inflows help in mitigating CO2 emissions and urbanization has insignificant effect. Based on the results, the Saudi government should encourage the FDI inflows to support a clean environment and should revise financial policies to mitigate the environmental problems of the financial sector in the Kingdom.